A wear-resistant and peel-resistant toy coating and preparation method thereof
By using components such as water-based polyurethane resin emulsion, water-based modified polyacrylate copolymer emulsion in toy coatings, combined with nanomaterials and natural pigments, the problems of insufficient wear resistance and peel resistance of traditional toy coatings are solved, and the effects of high wear resistance, peel resistance and safety and environmental protection are achieved.
Patent Information
- Application Number
- CN202411687903.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Traditional toy coatings have shortcomings in their wear resistance and peel resistance, and may contain harmful substances that affect children's health and the environment.
The coating is improved by combining nanomaterials and natural pigments through special preparation methods to improve the wear resistance, peel resistance, safety and environmental protection of the coating through special preparation methods.
It significantly improves the wear resistance, peel resistance and impact resistance of toy coatings, ensures the long-term stability and safety of the coating, and reduces potential harm to children's health and the environment.
Smart Images

Figure BDA0005150103230000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a wear-resistant and peeling-resistant toy coating and a preparation method thereof. Background Art
[0002] As people's living standards continue to improve, the demand for toys is becoming increasingly diversified. Toys are no longer just entertainment tools for children, but also products with multiple functions such as education and intellectual enlightenment. As an important part of toys, toy coatings must not only give toys bright colors and attractive appearance, but also have good performance to meet consumers' high requirements for toy quality.
[0003] Traditional toy paints often have some problems during use. On the one hand, the wear resistance is poor. When children play with toys, they will inevitably rub and collide with the toys. If the wear resistance of the toy paint is not good, it is easy to wear and fade, which not only affects the appearance of the toy, but also may reduce the service life of the toy.
[0004] On the other hand, the anti-peeling performance is insufficient. During the use of toys, they may be affected by environmental factors such as temperature changes and humidity changes, as well as improper operation by children, such as tearing, chewing, etc. If the anti-peeling performance of the toy paint is not good, the paint is prone to peeling. This will not only make the toy ugly, but also may cause harm to children's health. The peeling paint fragments may be swallowed by children by mistake, causing safety problems.
[0005] In addition, with the increasing awareness of environmental protection, people have also put forward higher requirements for the environmental friendliness of toy coatings. Traditional toy coatings may contain some harmful substances, such as heavy metals, volatile organic compounds, etc. These substances not only pollute the environment, but also may have adverse effects on children's health. Long-term exposure to toy coatings containing heavy metals may cause children to have symptoms of poisoning and affect their growth and development.
[0006] Therefore, it is necessary to continuously develop and improve coating technology in terms of wear resistance, anti-peeling, safety and environmental protection, so as to meet the increasingly high requirements of modern society for toy coatings and provide better quality toy products for children's growth. Summary of the invention
[0007] In order to improve the wear resistance, peeling resistance, safety and environmental protection of toy coatings, to meet the increasingly high requirements of modern society for toy coatings, and to provide better quality toy products for children's growth. The present invention provides a wear-resistant and peeling-resistant toy coating and a preparation method thereof. The present invention uses aqueous polyurethane resin emulsion, aqueous modified polyacrylate copolymer emulsion, styrene-stearyl methacrylate cross-linked polymer, castor oil isostearate succinate, serrata frankincense resin extract, dipentaerythritol hexahydroxystearate, stearyl beeswax ester, composite emulsifier, nano silicon carbide, nano alumina, nano bentonite, polytetrafluoroethylene powder, silane coupling agent and other ingredients as raw materials, and prepares the coating by a special method. The coating has good wear resistance, peeling resistance, impact resistance, safety and environmental protection, good protection of the substrate, and long service life. It is a high-quality toy product coating. Its specific technical scheme is as follows:
[0008] A wear-resistant and peel-resistant toy paint, the paint comprising the following raw materials in parts by mass: 40 to 50 parts of waterborne polyurethane resin emulsion, 5 to 10 parts of waterborne modified polyacrylate copolymer emulsion, 2 to 5 parts of styrene-stearyl methacrylate cross-linked polymer, 0.5 to 1.5 parts of castor oil isostearate succinate, 0.5 to 1.5 parts of serrata frankincense resin extract, 1 to 3 parts of dipentaerythritol hexahydroxystearate, 0.3 to 0.5 parts of stearyl beeswax ester, 3 to 5 parts of composite emulsifier, 3 to 8 parts of nano silicon carbide, 5 to 8 parts of nano alumina, 2 to 5 parts of nano bentonite, 2 to 5 parts of polytetrafluoroethylene micropowder, 3 to 5 parts of silane coupling agent, 3 to 8 parts of pigment, 1 to 2 parts of leveling agent, 1 to 2 parts of defoaming agent, 0.5 to 1 part of thickener and 10 to 20 parts of water.
[0009] In the above coating, the composite emulsifier includes EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine, and the mass ratio is EL-40 emulsifier: EMULGEN 1150S-60 emulsifier: cocamidopropyl betaine = (1-2): (3-6): (0.5-1.5).
[0010] In the above coating, the median particle size of the nano-silicon carbide is 30nm to 100nm.
[0011] In the above coating, the median particle size of the nano-aluminum oxide is 20nm to 100nm.
[0012] In the above coating, the median particle size of the nano-bentonite is 20nm to 50nm.
[0013] In the above coating, the median particle size of the polytetrafluoroethylene powder is 10 μm to 30 μm.
[0014] In the above coating, the pigment is a natural plant pigment.
[0015] In the above coating, the thickener is sodium alginate or hydroxyethyl cellulose.
[0016] The method for preparing the above-mentioned wear-resistant and peel-resistant toy coating comprises the following steps:
[0017] S1: Mix styrene-stearyl methacrylate crosspolymer, castor oil isostearate succinate, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester according to parts by mass, heat to 70° C. to 80° C., and stir evenly to obtain a mixture A;
[0018] S2: uniformly mixing nano silicon carbide, nano alumina and nano bentonite by air flow according to their mass fractions to obtain a mixture B;
[0019] S3: Mixing the thickener and water according to parts by mass to obtain a thickened liquid C;
[0020] S4: Mix the aqueous polyurethane resin emulsion and the aqueous modified polyacrylate copolymer emulsion at 300r / min to 500r / min for 10 to 15min according to the mass fraction; then add the composite emulsifier and continue to mix at 600r / min to 700r / min for 10 to 15min; then add the leveling agent and defoamer and mix at 600r / min to 700r / min for 10 to 15min; then add the mixture B in 5 times, mixing each time The mixture is 20wt% of the mass of the mixture B, and after adding 20wt% of the mixture B each time, stirring and mixing at a speed of 800r / min to 1000r / min for 10min to 15min, until all the mixture B is added, stirring and mixing at a speed of 800r / min to 1000r / min for 20min to 30min, adding the silane coupling agent, stirring and mixing at a speed of 600r / min to 700r / min for 10min to 15min; then adding the mixture A, stirring and mixing at a speed of 600r / min to 700r / min for 10min to 15min; then adding the serrata resin extract, the pigment and the polytetrafluoroethylene powder, stirring and mixing at a speed of 600r / min to 700r / min for 15min to 20min, after the color is uniform, reducing the stirring speed to 300r / min to 500r / min, adding the thickening liquid C under stirring, and mixing for 10min to 15min; finally filtering with a filter screen to obtain the coating.
[0021] In S4 of the above preparation method, the mesh size of the filter is 100-200 meshes.
[0022] The present invention provides a wear-resistant and peel-resistant toy coating and a preparation method thereof, and the beneficial effects are as follows:
[0023] 1. The coating of the present invention comprises ingredients such as waterborne polyurethane resin emulsion, waterborne modified polyacrylate copolymer emulsion, styrene-stearyl alcohol methacrylate cross-linked polymer, castor oil isostearate succinate, serrata frankincense resin extract, dipentaerythritol hexahydroxystearate, stearyl alcohol beeswax ester, composite emulsifier, nano silicon carbide, nano alumina, nano bentonite, polytetrafluoroethylene micro powder, silane coupling agent, etc. Among them, waterborne polyurethane resin emulsion is the main film-forming substance, providing the basic physical properties of the coating. Waterborne modified polyacrylate copolymer emulsion helps to form a film, improves water resistance and wear resistance. Styrene-stearyl alcohol methacrylate cross-linked polymer enhances flexibility, wear resistance and impact resistance through a cross-linked structure. Castor oil isostearate succinate improves dispersibility and has a positive effect on flexibility, wear resistance and impact resistance. Serrata frankincense resin extract is conducive to improving flexibility, wear resistance and impact resistance. Pentaerythritol hexahydroxystearate improves the flexibility, wear resistance and impact resistance of the coating. Stearyl beeswax ester mainly enhances wear resistance and water resistance. Composite emulsifiers improve the uniformity and compatibility of coatings, thereby improving various properties such as anti-stripping. Nano silicon carbide, nano alumina, and nano bentonite are used as fillers to enhance physical properties such as hardness and wear resistance. Polytetrafluoroethylene micropowder can reduce the surface friction coefficient and improve wear resistance. Silane coupling agents enhance the bonding between inorganic fillers and organic resins.
[0024] 2. Water-based modified polyacrylate copolymer emulsion, whose molecular structure contains segments that can form hydrophobic regions, can prevent water penetration after film formation, thereby improving water resistance. The film formed by the copolymer emulsion has a certain toughness and strength, and can resist wear and tear when subjected to friction, thus improving wear resistance.
[0025] 3. Styrene-stearyl methacrylate cross-linked polymer, whose cross-linked structure can form a network structure between polymer molecular chains, which can absorb and disperse external forces, thereby improving impact resistance. The network structure enables the coating to deform to a certain extent without breaking when subjected to external forces, enhancing flexibility. It prevents wear particles on the coating surface from falling off and improves wear resistance.
[0026] 4. The molecular structure of castor oil isostearate succinate has good compatibility, which can reduce the surface tension of the coating system and make various components disperse better. Its flexible chain segment can increase the flexibility of the coating, buffer when subjected to external force, and thus improve impact resistance. It helps to form a smooth coating surface, reduce the friction coefficient, and improve wear resistance.
[0027] 5. The extract of frankincense resin interacts with other ingredients in the coating to form an elastic structure, improve flexibility, and form a protective film on the surface of the coating to enhance the coating's ability to resist wear, absorb part of the impact energy, and improve impact resistance.
[0028] 6. Dipentaerythritol hexahydroxystearate, the multiple hydroxyl groups in its molecules can form hydrogen bonds and other interactions with other components, increase the flexibility between molecular chains, and improve flexibility. It can enhance the cohesion of the coating, make the coating denser, and improve wear resistance. When impacted, it can absorb energy through its own structural deformation, enhancing impact resistance.
[0029] 7. Stearyl beeswax ester can form a protective film on the surface of the coating, which can reduce the friction coefficient of the surface and improve wear resistance. This protective film can prevent the entry of water, thereby improving water resistance.
[0030] 8. The composite emulsifier is composed of multiple ingredients, including EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine. Different ingredients have different emulsification properties and can act on different types of ingredients to improve dispersibility and uniformity. Compared with single-ingredient emulsifiers, composite emulsifiers have better emulsification effects, which improve the workability and compatibility between the ingredients, make the coating more tightly bonded, and reduce peeling. Because the ingredients are evenly dispersed, the coating structure formed is more regular, which helps to improve flexibility, wear resistance and impact resistance.
[0031] 9. Water-based modified polyacrylate copolymer emulsion, styrene-stearyl methacrylate cross-linked polymer, castor oil isostearate succinate, serrata frankincense resin extract, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester are used together. The components interact with each other, enhance the cohesion of the coating from the inside, form protection on the surface, and reduce the peeling of the coating due to external forces and other factors. Their flexible segments and structures complement each other, allowing the coating to deform to a greater extent without breaking. By forming a denser coating structure, reducing the surface friction coefficient and other methods, the wear resistance is jointly improved. It can absorb and disperse impact energy from different angles and synergistically improve the impact strength. By forming hydrophobic areas and protective films, it can jointly prevent the penetration of water and improve water resistance.
[0032] 10. In the preparation method, the ingredients such as styrene-stearyl methacrylate cross-linked polymer are mixed and heated to fully fuse to form mixture A, which provides basic ingredients for subsequent reactions, ensures that these ingredients are evenly mixed, and play their role in flexibility and other aspects. Nano silicon carbide and the like are mixed by airflow to obtain mixture B, so that the nanoparticles are evenly dispersed to ensure that they can be evenly distributed in the coating, effectively playing the role of enhancing hardness and wear resistance. The thickener is mixed with water to obtain thickening liquid C, which is convenient for subsequent adjustment of the viscosity of the coating. The aqueous polyurethane resin emulsion and the aqueous modified polyacrylate copolymer emulsion are stirred and mixed to mix the two main film-forming substances evenly, and then the composite emulsifier is added and stirred continuously, and other ingredients are gradually introduced to ensure that each ingredient is evenly dispersed in the system to form a uniform and stable coating system. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0034] Example 1
[0035] A wear-resistant and anti-flaking toy paint, the paint comprising the following raw materials in parts by mass: 45 parts of waterborne polyurethane resin emulsion, 7.5 parts of waterborne modified polyacrylate copolymer emulsion, 3 parts of styrene-stearyl methacrylate cross-linked polymer, 1 part of castor oil isostearate succinate, 1 part of serrata frankincense resin extract, 2 parts of dipentaerythritol hexahydroxystearate, 0.4 parts of stearyl beeswax ester, 4 parts of composite emulsifier, 5 parts of nano silicon carbide, 6.5 parts of nano alumina, 3 parts of nano bentonite, 3 parts of polytetrafluoroethylene micro powder, 4 parts of silane coupling agent, 5 parts of pigment, 1.5 parts of leveling agent, 1.5 parts of defoamer, 0.8 parts of thickener and 15 parts of water.
[0036] The composite emulsifier includes EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine, and the mass ratio is EL-40 emulsifier: EMULGEN 1150S-60 emulsifier: cocamidopropyl betaine = 1.5:4.5:1. The median particle size of nano silicon carbide is 30nm. The median particle size of nano alumina is 53nm. The median particle size of nano bentonite is 27nm. The median particle size of polytetrafluoroethylene micropowder is 16μm. The pigment is a natural plant pigment. The thickener is sodium alginate.
[0037] The method for preparing the above-mentioned wear-resistant and peel-resistant toy coating comprises the following steps:
[0038] S1: Mix styrene-stearyl methacrylate crosspolymer, castor oil isostearate succinate, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester according to their weight proportions, heat to 75° C., and mix evenly to obtain a mixture A;
[0039] S2: uniformly mixing nano silicon carbide, nano alumina and nano bentonite by air flow according to their mass fractions to obtain a mixture B;
[0040] S3: Mixing the thickener and water according to parts by mass to obtain a thickened liquid C;
[0041] S4: According to the mass fraction, the water-based polyurethane resin emulsion and the water-based modified polyacrylate copolymer emulsion were stirred and mixed at a speed of 400 r / min for 12 minutes; then the composite emulsifier was added, and the stirring and mixing was continued at a speed of 650 r / min for 12 minutes; then the leveling agent and the defoaming agent were added, and the stirring and mixing was continued at a speed of 650 r / min for 12 minutes; then the mixture B was added in 5 times, 20wt% of the mass of the mixture B was added each time, and after adding 20wt% of the mixture B each time, the mixture was stirred and mixed at a speed of 900 r / min for 12 minutes until all the mixture B was added, and after stirring and mixing at a speed of 900 r / min for 25 minutes, the silane coupling agent was added, and the mixture was stirred and mixed at a speed of 650 r / min for 12 minutes. n; then add mixture A, continue stirring and mixing at a speed of 650 r / min for 12 minutes; then add serrata resin extract, pigment and polytetrafluoroethylene powder, continue stirring and mixing at a speed of 650 r / min for 18 minutes. After the color is uniform, reduce the stirring speed to 400 r / min, add thickening liquid C while stirring, and mix for 12 minutes; finally filter with a 150-mesh filter to obtain the coating.
[0042] Example 2
[0043] A wear-resistant and anti-flaking toy paint, the paint comprising the following raw materials in parts by mass: 40 parts of waterborne polyurethane resin emulsion, 5 parts of waterborne modified polyacrylate copolymer emulsion, 2 parts of styrene-stearyl methacrylate cross-linked polymer, 0.5 parts of castor oil isostearate succinate, 0.5 parts of serrata frankincense resin extract, 1 part of dipentaerythritol hexahydroxystearate, 0.3 parts of stearyl beeswax ester, 3 parts of composite emulsifier, 3 parts of nano silicon carbide, 5 parts of nano alumina, 2 parts of nano bentonite, 2 parts of polytetrafluoroethylene micropowder, 3 parts of silane coupling agent, 3 parts of pigment, 1 part of leveling agent, 1 part of defoamer, 0.5 parts of thickener and 10 parts of water.
[0044] The composite emulsifier includes EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine, and the mass ratio is EL-40 emulsifier: EMULGEN 1150S-60 emulsifier: cocamidopropyl betaine = 1:3:0.5. The median particle size of nano silicon carbide is 65nm. The median particle size of nano alumina is 20nm. The median particle size of nano bentonite is 50nm. The median particle size of polytetrafluoroethylene micropowder is 21μm. The pigment is a natural plant pigment. The thickener is hydroxyethyl cellulose.
[0045] The method for preparing the above-mentioned wear-resistant and peel-resistant toy coating comprises the following steps:
[0046] S1: Mix styrene-stearyl methacrylate crosspolymer, castor oil isostearate succinate, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester according to parts by mass, heat to 70° C., and stir evenly to obtain a mixture A;
[0047] S2: uniformly mixing nano silicon carbide, nano alumina and nano bentonite by air flow according to their mass fractions to obtain a mixture B;
[0048] S3: Mixing the thickener and water according to parts by mass to obtain a thickened liquid C;
[0049] S4: According to the mass fraction, the waterborne polyurethane resin emulsion and the waterborne modified polyacrylate copolymer emulsion were stirred and mixed at a speed of 300 r / min for 10 min; then the composite emulsifier was added, and the stirring and mixing was continued at a speed of 600 r / min for 10 min; then the leveling agent and the defoaming agent were added, and the stirring and mixing was continued at a speed of 600 r / min for 10 min; then the mixture B was added in 5 times, 20wt% of the mass of the mixture B was added each time, and after adding 20wt% of the mixture B each time, the mixture was stirred and mixed at a speed of 800 r / min for 10 min until all the mixture B was added, and after stirring and mixing at a speed of 800 r / min for 20 min, the silane coupling agent was added, and the mixture was stirred and mixed at a speed of 600 r / min for 10 min. n; then add mixture A, continue stirring and mixing at a speed of 600 r / min for 10 minutes; then add serrata resin extract, pigment and polytetrafluoroethylene powder, continue stirring and mixing at a speed of 600 r / min for 15 minutes. After the color is uniform, reduce the stirring speed to 300 r / min, add thickening liquid C while stirring, and mix for 10 minutes; finally filter with a 100-mesh filter to obtain a coating.
[0050] Example 3
[0051] A wear-resistant and anti-flaking toy paint, the paint comprising the following raw materials in parts by mass: 40 parts of waterborne polyurethane resin emulsion, 10 parts of waterborne modified polyacrylate copolymer emulsion, 2 parts of styrene-stearyl methacrylate cross-linked polymer, 1.5 parts of castor oil isostearate succinate, 0.5 parts of serrata frankincense resin extract, 3 parts of dipentaerythritol hexahydroxystearate, 0.3 parts of stearyl beeswax ester, 5 parts of composite emulsifier, 3 parts of nano silicon carbide, 8 parts of nano alumina, 2 parts of nano bentonite, 5 parts of polytetrafluoroethylene micropowder, 3 parts of silane coupling agent, 8 parts of pigment, 1 part of leveling agent, 2 parts of defoamer, 0.5 parts of thickener and 14 parts of water.
[0052] The composite emulsifier includes EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine, and the mass ratio is EL-40 emulsifier: EMULGEN 1150S-60 emulsifier: cocamidopropyl betaine = 1:6:0.5. The median particle size of nano silicon carbide is 42nm. The median particle size of nano alumina is 55nm. The median particle size of nano bentonite is 20nm. The median particle size of polytetrafluoroethylene micropowder is 10μm. The pigment is a natural plant pigment. The thickener is hydroxyethyl cellulose.
[0053] The method for preparing the above-mentioned wear-resistant and peel-resistant toy coating comprises the following steps:
[0054] S1: Mix styrene-stearyl methacrylate crosspolymer, castor oil isostearate succinate, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester according to parts by mass, heat to 70° C., and stir evenly to obtain a mixture A;
[0055] S2: uniformly mixing nano silicon carbide, nano alumina and nano bentonite by air flow according to their mass fractions to obtain a mixture B;
[0056] S3: Mixing the thickener and water according to parts by mass to obtain a thickened liquid C;
[0057] S4: According to the mass fraction, the aqueous polyurethane resin emulsion and the aqueous modified polyacrylate copolymer emulsion were stirred and mixed at a speed of 500 r / min for 10 min; then the composite emulsifier was added, and the stirring and mixing was continued at a speed of 700 r / min for 10 min; then the leveling agent and the defoaming agent were added, and the stirring and mixing was continued at a speed of 700 r / min for 10 min; then the mixture B was added in 5 times, 20wt% of the mass of the mixture B was added each time, and after each addition of 20wt% of the mixture B, the mixture was stirred and mixed at a speed of 1000 r / min for 10 min until all the mixture B was added. After the mixture is mixed at a speed of 1000 r / min for 20 min, a silane coupling agent is added, and the mixture is mixed at a speed of 700 r / min for 10 min; then mixture A is added, and the mixture is mixed at a speed of 700 r / min for 10 min; then the extract of frankincense resin, pigment and polytetrafluoroethylene powder are added, and the mixture is mixed at a speed of 700 r / min for 15 min. After the color is uniform, the stirring speed is reduced to 500 r / min, and thickening liquid C is added under stirring, and the mixture is mixed for 10 min. Finally, the mixture is filtered through a 200-mesh filter to obtain a coating.
[0058] Example 4
[0059] A wear-resistant and anti-flaking toy paint, the paint comprising the following raw materials in parts by mass: 50 parts of waterborne polyurethane resin emulsion, 10 parts of waterborne modified polyacrylate copolymer emulsion, 5 parts of styrene-stearyl methacrylate cross-linked polymer, 1.5 parts of castor oil isostearate succinate, 1.5 parts of serrata frankincense resin extract, 3 parts of dipentaerythritol hexahydroxystearate, 0.5 parts of stearyl beeswax ester, 5 parts of composite emulsifier, 8 parts of nano silicon carbide, 8 parts of nano alumina, 5 parts of nano bentonite, 5 parts of polytetrafluoroethylene micropowder, 5 parts of silane coupling agent, 8 parts of pigment, 2 parts of leveling agent, 2 parts of defoamer, 1 part of thickener and 20 parts of water.
[0060] The composite emulsifier includes EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine, and the mass ratio is EL-40 emulsifier: EMULGEN 1150S-60 emulsifier: cocamidopropyl betaine = 2:6:1.5. The median particle size of nano silicon carbide is 82nm. The median particle size of nano alumina is 100nm. The median particle size of nano bentonite is 43nm. The median particle size of polytetrafluoroethylene micropowder is 30μm. The pigment is a natural plant pigment. The thickener is hydroxyethyl cellulose.
[0061] The method for preparing the above-mentioned wear-resistant and peel-resistant toy coating comprises the following steps:
[0062] S1: Mix styrene-stearyl methacrylate crosspolymer, castor oil isostearate succinate, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester according to parts by mass, heat to 80° C., and stir evenly to obtain a mixture A;
[0063] S2: uniformly mixing nano silicon carbide, nano alumina and nano bentonite by air flow according to their mass fractions to obtain a mixture B;
[0064] S3: Mixing the thickener and water according to parts by mass to obtain a thickened liquid C;
[0065] S4: According to the mass fraction, the aqueous polyurethane resin emulsion and the aqueous modified polyacrylate copolymer emulsion were stirred and mixed at a speed of 500 r / min for 15 minutes; then the composite emulsifier was added, and the stirring and mixing was continued at a speed of 700 r / min for 15 minutes; then the leveling agent and the defoaming agent were added, and the stirring and mixing was continued at a speed of 700 r / min for 15 minutes; then the mixture B was added in 5 times, 20wt% of the mass of the mixture B was added each time, and after each addition of 20wt% of the mixture B, the mixture was stirred and mixed at a speed of 1000 r / min for 15 minutes until all the mixture B was added. After the mixture is mixed at a speed of 1000 r / min for 30 minutes, a silane coupling agent is added, and the mixture is mixed at a speed of 700 r / min for 15 minutes; then mixture A is added, and the mixture is mixed at a speed of 700 r / min for 15 minutes; then the extract of frankincense resin, pigment and polytetrafluoroethylene powder are added, and the mixture is mixed at a speed of 700 r / min for 20 minutes. After the color is uniform, the stirring speed is reduced to 500 r / min, and thickening liquid C is added under stirring, and the mixture is mixed for 15 minutes; finally, the mixture is filtered through a 200-mesh filter to obtain a coating.
[0066] Example 5
[0067] A wear-resistant and anti-flaking toy paint, the paint comprising the following raw materials in parts by mass: 50 parts of waterborne polyurethane resin emulsion, 5 parts of waterborne modified polyacrylate copolymer emulsion, 5 parts of styrene-stearyl methacrylate cross-linked polymer, 0.5 parts of castor oil isostearate succinate, 1.5 parts of serrata frankincense resin extract, 1 part of dipentaerythritol hexahydroxystearate, 0.5 parts of stearyl beeswax ester, 3 parts of composite emulsifier, 8 parts of nano silicon carbide, 5 parts of nano alumina, 5 parts of nano bentonite, 2 parts of polytetrafluoroethylene micropowder, 5 parts of silane coupling agent, 3 parts of pigment, 2 parts of leveling agent, 1 part of defoamer, 1 part of thickener and 18 parts of water.
[0068] The composite emulsifier includes EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine, and the mass ratio is EL-40 emulsifier: EMULGEN 1150S-60 emulsifier: cocamidopropyl betaine = 2:3:1.5. The median particle size of nano silicon carbide is 100nm. The median particle size of nano alumina is 79nm. The median particle size of nano bentonite is 35nm. The median particle size of polytetrafluoroethylene micropowder is 13μm. The pigment is a natural plant pigment. The thickener is sodium alginate.
[0069] The method for preparing the above-mentioned wear-resistant and peel-resistant toy coating comprises the following steps:
[0070] S1: Mix styrene-stearyl methacrylate crosspolymer, castor oil isostearate succinate, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester according to parts by mass, heat to 80° C., and stir evenly to obtain a mixture A;
[0071] S2: uniformly mixing nano silicon carbide, nano alumina and nano bentonite by air flow according to their mass fractions to obtain a mixture B;
[0072] S3: Mixing the thickener and water according to parts by mass to obtain a thickened liquid C;
[0073] S4: According to the mass fraction, the waterborne polyurethane resin emulsion and the waterborne modified polyacrylate copolymer emulsion were stirred and mixed at a speed of 300 r / min for 15 minutes; then the composite emulsifier was added, and the stirring and mixing was continued at a speed of 600 r / min for 15 minutes; then the leveling agent and the defoaming agent were added, and the stirring and mixing was continued at a speed of 600 r / min for 15 minutes; then the mixture B was added in 5 times, 20wt% of the mass of the mixture B was added each time, and after adding 20wt% of the mixture B each time, the mixture was stirred and mixed at a speed of 800 r / min for 15 minutes until all the mixture B was added, and after stirring and mixing at a speed of 800 r / min for 30 minutes, the silane coupling agent was added, and the mixture was stirred and mixed at a speed of 600 r / min for 15 minutes. n; then add mixture A, continue stirring and mixing at a speed of 600 r / min for 15 minutes; then add serrata resin extract, pigment and polytetrafluoroethylene powder, continue stirring and mixing at a speed of 600 r / min for 20 minutes. After the color is uniform, reduce the stirring speed to 300 r / min, add thickening liquid C while stirring, and mix for 15 minutes; finally filter with a 100-mesh filter to obtain a coating.
[0074] The model of the aqueous polyurethane resin emulsion used in the above embodiments is YC-305, which is derived from Anhui Yuanchen New Materials Technology Co., Ltd. The model of the aqueous modified polyacrylate copolymer emulsion is IRW-E007, which is a modified styrene-butyl acrylate copolymer, which is derived from Yingchuang Technology (Guangdong) Co., Ltd. Styrene-stearyl methacrylate cross-linked polymer is derived from Hubei Qifei Pharmaceutical Chemical Co., Ltd. Castor oil isostearate succinate is derived from Zhongshan Aikai Chemical Technology Co., Ltd. The extract of frankincense resin contains 65wt% of frankincense acid and is derived from Shaanxi Zhenhe Biotechnology Co., Ltd. Dipentaerythritol hexahydroxystearate and stearyl beeswax ester are both derived from Xi'an Shengqintang New Materials Co., Ltd. The model of the silane coupling agent is KH-561, which is derived from Shandong Bosheng Chemical Co., Ltd. The leveling agent is Dow Corning DC-57 leveling agent. The defoamer is Deqian 5800F defoamer. Sodium alginate is derived from Jinan Hongtu Chemical Co., Ltd. The model of hydroxyethyl cellulose is QP-100MH, which comes from Dow Chemical (Shanghai) Co., Ltd.
[0075] Comparative Example 1
[0076] No water-based modified polyacrylate copolymer emulsion is added to the coating, and the content of the water-based modified polyacrylate copolymer emulsion is replaced by water-based polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0077] Comparative Example 2
[0078] No styrene-stearyl methacrylate cross-linked polymer is added to the coating, and the content of styrene-stearyl methacrylate cross-linked polymer is replaced by waterborne polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0079] Comparative Example 3
[0080] No castor oil isostearate succinate is added to the coating, and the content of castor oil isostearate succinate is replaced by waterborne polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0081] Comparative Example 4
[0082] No Boswellia serrata resin extract is added to the coating, and the content of Boswellia serrata resin extract is replaced by waterborne polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0083] Comparative Example 5
[0084] No dipentaerythritol hexahydroxystearate is added to the coating, and the content of dipentaerythritol hexahydroxystearate is replaced by an aqueous polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0085] Comparative Example 6
[0086] No stearyl beeswax ester is added to the coating, and the content of stearyl beeswax ester is replaced by an aqueous polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0087] Comparative Example 7
[0088] No composite emulsifier is added to the coating, and the content of the composite emulsifier is replaced by an aqueous polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0089] Comparative Example 8
[0090] The composite emulsifier was replaced by EL-40 emulsifier; other parameters and methods were the same as in Example 1.
[0091] Comparative Example 9
[0092] The composite emulsifier was replaced by EMULGEN 1150S-60 emulsifier; other parameters and methods were the same as in Example 1.
[0093] Comparative Example 10
[0094] The coating does not contain water-based modified polyacrylate copolymer emulsion, styrene-stearyl methacrylate cross-linked polymer, castor oil isostearate succinate, serrata frankincense resin extract, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester, and the content of each component is replaced by water-based polyurethane resin emulsion; other parameters and methods are the same as in Example 1.
[0095] The coatings of the above-mentioned embodiments and comparative examples were tested.
[0096] Test plate: The substrate is a bottom carbon steel plate, the coatings are the coatings of each embodiment and each comparative example, the coating thickness is 160 μm, and the steel plate scraping method is carried out in accordance with GB / T 1727 "General Preparation Method for Paint Film".
[0097] 1. Paint Screening
[0098] In the last step of preparation, the residue on the sieve after the coating was sieved was observed, and the results are shown in Table 1 below.
[0099] 2. Detection of harmful substances content
[0100] For VOC content, gas chromatography and gas chromatography-mass spectrometry were used to separate and quantitatively analyze the volatile organic compounds in the paint samples; free formaldehyde content was determined by acetylacetone spectrophotometry, where formaldehyde reacts with acetylacetone to generate colored compounds, and then the absorbance was measured with a spectrophotometer to calculate the formaldehyde content; heavy metal content was determined by atomic absorption spectrometry and inductively coupled plasma emission spectrometry, where the paint samples were digested and the contents of various heavy metal elements were determined. After testing, the content of harmful substances in the paint met the environmental protection requirements and the limit requirements of GB 24613-2009, and was harmless to children's health.
[0101] 3. Anti-peeling test
[0102] According to GB / T 9286 "Cross-cut Test for Paint and Varnish Film", use a cross-cut tool to cross-cut the surface of the test panel with a spacing of 2mm; after crossing, tape is applied to the cross-cut area, and then the tape is quickly torn off to observe the peeling of the coating and grade the peeling resistance. Peeling resistance evaluation level: Level 0 - the cut edge is completely smooth, and no squares are peeled off. Level 1 - A small amount of coating peels off at the intersection of the cuts, but the affected cross-cut area cannot be significantly greater than 5%. Level 2 - The coating peels off at the intersection of the cuts or along the edges of the cuts, and the affected cross-cut area is significantly greater than 5%, but not significantly greater than 15%. Level 3 - The coating partially or completely peels off in large pieces along the cut edge, and / or partially or completely peels off at different parts of the grid, and the affected cross-cut area is significantly greater than 15%, but not significantly greater than 35%. Level 4 - The coating peels off in large pieces along the cut edge, and / or some squares partially or completely peel off, and the affected cross-cut area is significantly greater than 35%, but not significantly greater than 65%. Grade 5: The degree of peeling exceeded Grade 4. The results are shown in Table 1 below.
[0103] 4. Flexibility test
[0104] According to GB / T 1731 "Determination of paint film flexibility", the test plate coated with the coating is placed on the flexibility tester, and a shaft is used to apply pressure on the test plate to bend the test plate, and observe whether the coating has cracks or peeling. The flexibility evaluation level is excellent: the paint film has no damage when bent on a shaft with a diameter of 1mm; good: the paint film is intact when bent on a shaft with a diameter of 2mm to 3mm; medium: the paint film is intact when bent on a shaft with a diameter of 4mm to 5mm; poor: there are slight signs of damage when bent on a shaft with a diameter of 6mm to 8mm, and the paint film has slight reticulation or cracks; very poor: the paint film has reticulation, cracks or peeling when bent on a shaft with a diameter of more than 8mm. The results are shown in Table 1.
[0105] 5. Wear resistance test
[0106] According to GBT 23988 "Determination of Wear Resistance of Coatings by Falling Sand Method", the abrasive is selected as natural quartz sand according to the specification, the abrasive volume for each impact is 2L, the impact height is 1m, until a 4mm diameter is exposed on the substrate, and the wear resistance is calculated based on the abrasive consumption. The results are shown in Table 1 below.
[0107] 6. Impact strength test
[0108] According to GB / T 1732 "Determination of impact resistance of paint film", a paint film impactor with a weight of 1000g is used, the depth of the punch entering the groove is 0.1cm, the scale of the slide is 50.0cm±0.1cm, and the division is 1cm. The weight is raised to a height of 20cm, and then it is allowed to fall freely to impact the paint film on the test plate. If there is no damage, the impact height is gradually increased by 5cm each time until the paint film shows cracks, wrinkles, shedding and other damage phenomena, and the maximum impact height is recorded. The distance between each impact point is not less than 15mm, and not less than 15mm from the edge of the test plate. The results are shown in Table 1 below.
[0109] 7. Water resistance test
[0110] According to GB / T 1733 "Determination of Water Resistance of Paint Film", the test plate is placed in deionized water, 2 / 3 of the test plate is immersed in water, and the water temperature is maintained at 25°C; after 120 hours, observe whether the test plate has blistering, peeling, or rusting. Evaluation level, level 1: the paint film remains completely original, and the paint film does not have any gloss loss, discoloration, blistering, wrinkling, shedding, rusting, etc.; level 2: the paint film surface has slight changes, such as slight gloss loss and slightly lighter color, but does not affect the overall performance and appearance of the paint film; level 3: the paint film surface has obvious changes, with obvious gloss loss, discoloration, blistering, wrinkling, etc., but has not yet reached the level of serious damage; level 4: the paint film has serious blistering, peeling, rusting, etc., and the water resistance of the paint film is very poor and cannot meet the use requirements. The results are shown in Table 1 below.
[0111] Table 1 Coating test results
[0112]
[0113] As can be seen from the above results, the coatings of Examples 1 to 5 have good dispersibility, excellent anti-flaking, good wear resistance, high impact strength, good flexibility, and are safe and non-toxic. As can be seen from the results of Comparative Example 1, the water-based modified polyacrylate copolymer emulsion can significantly improve the water resistance of the coating, and help improve the wear resistance of the coating. As can be seen from the results of Comparative Example 2, styrene-stearyl alcohol methacrylate cross-linked polymer can significantly improve the flexibility of the coating, and help improve the wear resistance and impact resistance of the coating. As can be seen from the results of Comparative Example 3, castor oil isostearate succinate can improve the dispersion of coating components, promote coating uniformity, and then help improve the flexibility, wear resistance and impact resistance of the coating. As can be seen from the results of Comparative Example 4, the extract of serrata frankincense resin helps improve the flexibility, wear resistance and impact resistance of the coating. As can be seen from the results of Comparative Example 5, dipentaerythritol hexahydroxystearate helps improve the flexibility, wear resistance and impact resistance of the coating. As shown in the results of Comparative Example 6, stearyl beeswax ester helps to improve the wear resistance and water resistance of the coating. As shown in the results of Comparative Examples 7 to 9, the composite emulsifier has a better dispersion and emulsification effect on each component in the coating system than the emulsifier of a single component, greatly improves the composition and workability of the coating, has good compatibility, and can greatly improve the coating quality, reduce and avoid defects, and improve the anti-flaking, flexibility, wear resistance and impact resistance of the coating. As shown in the results of Comparative Example 10, the coating system does not add water-based modified polyacrylate copolymer emulsion, styrene-stearyl methacrylate cross-linked polymer, castor oil isostearate succinate, serrata frankincense resin extract, dipentaerythritol hexahydroxystearate, stearyl beeswax ester, which greatly affects the various properties of the coating.
Claims
1. A wear-resistant and peel-resistant toy paint, characterized in that: The coating comprises the following raw materials in parts by mass: 40 to 50 parts of waterborne polyurethane resin emulsion, 5 to 10 parts of waterborne modified polyacrylate copolymer emulsion, 2 to 5 parts of styrene-stearyl methacrylate cross-linked polymer, 0.5 to 1.5 parts of castor oil isostearate succinate, 0.5 to 1.5 parts of serrata resin extract, 1 to 3 parts of dipentaerythritol hexahydroxystearate, 0.3 to 0.5 parts of stearyl beeswax ester, 3 to 5 parts of composite emulsifier, 3 to 8 parts of nano silicon carbide, 5 to 8 parts of nano alumina, 2 to 5 parts of nano bentonite, 2 to 5 parts of polytetrafluoroethylene micropowder, 3 to 5 parts of silane coupling agent, 3 to 8 parts of pigment, 1 to 2 parts of leveling agent, 1 to 2 parts of defoaming agent, 0.5 to 1 part of thickener and 10 to 20 parts of water.
2. A wear-resistant and peel-resistant toy paint according to claim 1, characterized in that: The composite emulsifier includes EL-40 emulsifier, EMULGEN 1150S-60 emulsifier and cocamidopropyl betaine, and the mass ratio is EL-40 emulsifier: EMULGEN 1150S-60 emulsifier: cocamidopropyl betaine = (1-2): (3-6): (0.5-1.5).
3. The wear-resistant and peel-resistant toy paint according to claim 1, characterized in that: The median particle size of the nano silicon carbide is 30nm to 100nm.
4. The wear-resistant and peel-resistant toy paint according to claim 1, characterized in that: The median particle size of the nano-alumina is 20nm-100nm.
5. The wear-resistant and peel-resistant toy paint according to claim 1, characterized in that: The median particle size of the nano bentonite is 20nm to 50nm.
6. The wear-resistant and peel-resistant toy paint according to claim 1, characterized in that: The median particle size of the polytetrafluoroethylene powder is 10 μm to 30 μm.
7. The wear-resistant and peel-resistant toy paint according to claim 1, characterized in that: The pigment is a natural plant pigment.
8. The wear-resistant and peel-resistant toy paint according to claim 1, characterized in that: The thickener is sodium alginate or hydroxyethyl cellulose.
9. A method for preparing a wear-resistant and anti-flaking toy coating, used for preparing a wear-resistant and anti-flaking toy coating as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1: Mix styrene-stearyl methacrylate crosspolymer, castor oil isostearate succinate, dipentaerythritol hexahydroxystearate, and stearyl beeswax ester according to parts by mass, heat to 70° C. to 80° C., and stir evenly to obtain a mixture A; S2: uniformly mixing nano silicon carbide, nano alumina and nano bentonite by air flow according to their mass fractions to obtain a mixture B; S3: Mixing the thickener and water according to parts by mass to obtain a thickened liquid C; S4: According to the mass fraction, the aqueous polyurethane resin emulsion and the aqueous modified polyacrylate copolymer emulsion are stirred and mixed at a speed of 300r / min to 500r / min for 10min to 15min; then the composite emulsifier is added, and the stirring and mixing is continued at a speed of 600r / min to 700r / min for 10min to 15min; then the leveling agent and the defoaming agent are added, and the stirring and mixing is continued at a speed of 600r / min to 700r / min for 10min to 15min; then the mixture B is added in 5 times, 20wt% of the mass of the mixture B is added each time, and after each addition of 20wt% of the mixture B, the mixture is stirred and mixed at a speed of 800r / min to 1000r / min for 10min to 15min, until all the mixture B is added, and the mixture is stirred at 800r / min to 1000r / min for 10min to 15min. After stirring and mixing at a speed of r / min to 1000r / min for 20min to 30min, a silane coupling agent is added, and stirring and mixing is carried out at a speed of 600r / min to 700r / min for 10min to 15min; then, mixture A is added, and stirring and mixing is continued at a speed of 600r / min to 700r / min for 10min to 15min; then, serrata frankincense resin extract, pigment and polytetrafluoroethylene powder are added, and stirring and mixing is continued at a speed of 600r / min to 700r / min for 15min to 20min. After the color is uniform, the stirring speed is reduced to 300r / min to 500r / min, and thickening liquid C is added in the stirring state, and mixing is carried out for 10min to 15min; finally, filtering is carried out through a filter to obtain a coating.
10. The method for preparing a wear-resistant and peel-resistant toy coating according to claim 9, characterized in that: In S4, the mesh size of the filter is 100-200 meshes.
Citation Information
Patent Citations
Method for preparing model coating for children
CN106280873A
Anti-impact high-weather-resistant water-based industrial paint and preparation method thereof
CN106833200A